AKULTURASI GAYA ARSITEKTUR KOLONIAL DAN CINA PADA BANGUNAN ROTI MRUYUNG, KOTA LAMA BANYUMAS - Eva Priyanti; Revi Aulia Purbandini; Artanti Kusuma Ayu (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
This study explores the architectural acculturation between Colonial and traditional Chinese styles as manifested in the Roti Mruyung building in Banyumas, a historic structure that reflects the intersection of two distinct cultural identities. This architectural fusion represents the socio-cultural dynamics of the colonial era and the interaction between the Chinese ethnic community and the local population. A descriptive qualitative method was employed to identify and analyze the architectural elements that demonstrate this stylistic blend. Data were collected through direct observation of the building's physical features, interviews with the building's owners and local cultural figures, and a literature review of relevant sources on colonial and Chinese architecture. The findings reveal that Roti Mruyung incorporates colonial architectural elements such as symmetrical layouts, large openings, and brick construction, which are harmoniously combined with traditional Chinese features, including ornaments, and other interior elements. This research highlights that architectural acculturation in the Roti Mruyung building is not only aesthetic but also rich in historical significance and cultural identity, underscoring the importance of its preservation.